2020
DOI: 10.1016/j.vaccine.2020.02.089
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of improved immune complex and virus-like particle vaccines containing Zika virus envelope domain III synergistically enhances immunogenicity

Abstract: a b s t r a c tZika virus (ZIKV) reemergence poses a significant health threat especially due to its risks to fetal development, necessitating safe and effective vaccines that can protect pregnant women. Zika envelope domain III (ZE3) has been identified as a safe and effective vaccine candidate, however it is poorly immunogenic. We previously showed that plant-made recombinant immune complex (RIC) vaccines are a robust platform to improve the immunogenicity of weak antigens. In this study, we altered the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The construction of a geminiviral replicon plant expression vector for ZE3, as well as its fusion to the 6D8 C-terminus (pBYR11eM-h6D8ZE3, referred to here as construct “HLZe”) or N-terminus with epitope tag (pBYR11eMa-BAZE3-Hgp371) or without epitope tag (pBYR11eMa-BAZE3-H) have been previously described (Diamos et al, 2020b, 2020a) A vector pBYKEMd2-6D8 expressing the full 6D8 mAb without ZE3 fusion (construct “HL”) has been previously described (Diamos et al, 2020b, 2020a). To create a vector expressing only the light chain of 6D8, pBYKEMd2-6D8 was digested with XhoI and the vector was self-ligated to yield pBYKEMd-6D8K.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of a geminiviral replicon plant expression vector for ZE3, as well as its fusion to the 6D8 C-terminus (pBYR11eM-h6D8ZE3, referred to here as construct “HLZe”) or N-terminus with epitope tag (pBYR11eMa-BAZE3-Hgp371) or without epitope tag (pBYR11eMa-BAZE3-H) have been previously described (Diamos et al, 2020b, 2020a) A vector pBYKEMd2-6D8 expressing the full 6D8 mAb without ZE3 fusion (construct “HL”) has been previously described (Diamos et al, 2020b, 2020a). To create a vector expressing only the light chain of 6D8, pBYKEMd2-6D8 was digested with XhoI and the vector was self-ligated to yield pBYKEMd-6D8K.…”
Section: Methodsmentioning
confidence: 99%
“…More than 69 countries have reported Zika virus infections [ 214 ] between 2015 and 2017. In 2016, the World Health Organization declared the Zika virus infections as a Public Health Emergency of International Concern.…”
Section: Zika Virus Vaccinesmentioning
confidence: 99%
“…The construction of a geminiviral replicon plant expression vector for ZE3, as well as its fusion to the 6D8 C-terminus (pBYR11eM-h6D8ZE3, referred to here as construct "HLZe") or N-terminus with epitope tag (pBYR11eMa-BAZE3-Hgp371) or without epitope tag (pBYR11eMa-BAZE3-H) have been previously described (27,31) A vector pBYKEMd2-6D8 expressing the full 6D8 mAb without ZE3 fusion (construct "HL") has been previously described (27,31). To create a vector expressing only the light chain of 6D8, pBYKEMd2-6D8 was digested with XhoI and the vector was self-ligated to yield pBYKEMd-6D8K.…”
Section: Experimental Procedures Vector Constructionmentioning
confidence: 99%
“…The resulting molecules self-interact and form highly immunogenic antigen-antibody clusters. Past research has shown the potential for RIC-like molecules to produce promising vaccine candidates for Clostridium tetani (21), Ebola virus (22,23), Mycobacterium tuberculosis (24), dengue virus (25), human papillomavirus (26) and Zika virus (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation